Ensino de cônicas - Domingues, Ana Clara de Lima (2022)
Among the mathematical content, conics is seen briefly, according to the Common National Curriculum Base. However, among the aspects of mathematics, perhaps it is quite present in our daily lives. We can find their curves in receiving paraboloids like satellite dishes or emitters like lanterns, we can find them in the path of celestial elements like planets, asteroids and satellites or particles in the electric field. Its study can be applied in several areas of knowledge, such as architecture, astronomy, physics, engineering, etc. Seeing how important this content is, this work’s objective is to facilitate the Teaching of Conics through an auxiliary text, structured with its theory, historical context, examples, exercises and application in everyday life. We will also use GeoGebra software and Concrete Material, in order to make learning more attractive.